Answer:
0.02
Step-by-step explanation:
This is a quadratic formula with a general form of a²x + bx + c = 0. For quadratic equations, we can solve for its two roots using the quadratic formula shown in the attached picture.
a = -3
b = -4
c = -4
x = [-(-4) + √(-4)² - 4(-3)(-4)]/2(-3) =
<em>2 + √-32/2</em>x = [-(-4) - √(-4)² - 4(-3)(-4)]/2(-3) =
<em> 2 - √-32/2</em>
2x2−5x=3
I think the first step would be to
Subtract 3 from both sides
2x2−5x−3=3−3
2x2−5x−3=0
Then
For this equation: a=2, b=-5, c=-3
2x2+−5x+−3=0
Lastly you would
Use quadratic formula with a=2, b=-5, c=-3
I think your answer would then have to be...
x = 3 or x = −1
/2
Answer:
hello :
Step-by-step explanation:
f(x) = 2x²+5√(x-2)
f(x) exist : x - 2 ≥ 0 : x ≥ 2
The domain for f(x) is all real numbers "greater" than or equal to 2
Well plug 0 in for x and solve for y and that is the vertex of your expression